Effect of bispectral index-guided total intravenous anesthesia in younger children: A prospective, randomized, controlled trial - Liu, Guoliang; Zhang, Jianmin; Wang, Fang; Li, Lijing; Zhang, Xuemei (Frontiers in Neurology, 2022)
Background BIS-guided total intravenous anesthesia (TIVA) is widely used in children, but few studies have attempted to evaluation of the effect of BIS-guided TIVA in younger children. This study aimed to evaluate the effect of bispectral index (BIS) guidance during TIVA in younger children during anesthesia. Methods This study is a prospective, randomized, single-blind and controlled clinical trial. This study enrolled pediatric patients (aged 1–3 years) who were scheduled for surgery under TIVA with propofol and remifentanil. The children were randomly assigned to the BIS group (group B) and standard clinical practice group (group S). The BIS values in group B were maintained at 45–60. The anesthesiologist controlled the depth of anesthesia in group S according to the variation in the clinical signs of the children. The time of extubation, duration of stay in post-anesthesia care unit (PACU), as well as BIS values, heart rate (HR), mean arterial pressure (MAP), pulse oxygen saturation at eight time points 1 min before induction (T1), 1 min after induction (1 min after the induction drugs were administrated) (T2), immediately after intubation (T3), immediately after skin incision (T4), 30 min after the start of the operation (T5), 60 min after the start of operation (T6), immediately after drug withdrawal (T7), and immediately after extubation (T8), propofol consumption, and postoperative adverse reactions were recorded. Results There was no significant difference in time to extubation 15(10,21) vs 14 (11,20) and duration of stay in PACU 27 (20,37) vs. 29 (22,39) between the group B and group S. At the time points 30 min after the start of the operation, 60 min after the start of operation and immediately after drug withdrawal, the BIS values in group S were significantly higher than those in group B (57 ± 9, 57 ± 9, 60 ± 8 vs 52 ± 7, 54 ± 7, 57 ± 6). Conclusions The use of BIS-guided total intravenous anesthesia in younger children does not shorten the time of extubation and the duration of stay in the PACU. Trial registration Chictr.org.cn identifier: 24/11/2017, ChiCTR-IOR-17013530.